A strategic management plan for Central Mindanao Colleges (2012-2017) - Quiambao, Victor G., Jr (School of Management, University of the Philippines Mindanao, 2011)
This Policy and Strategic Management Plan is a five-year plan for Central Mindanao Colleges (CMC). It aimed to create a blueprint of identified strategies that shall address the looming challenges which CMC is facing. The first chapter presents an overview of the corporation. A general situational review was conducted to determine the current state of CMC and its perceived problems. The second and third chapters on the other hand, are an analysis of the external and internal factors which directly and indirectly affect the corporation. Several tools were used to aid in arriving at a deeper analysis of the environment to where the corporation belongs. An analysis of the remote environment which includes the Political, Economic, Social, Technological, Legal, and Environmental aspects were specified. The industry environment was analyzed following the Porter?s five forces model which includes the identification of threats of new entrants, buyer power, supplier power, threat of substitutes, and rivalry. An analysis of the competitors and the customers was also conducted in considering the operating environment of the corporation. The functional areas of the corporation namely the General Management, Human resources, Finance and Marketing were also considered in arriving at a deeper analysis of the internal environment. Lastly, an enumeration of CMC?s Strengths, Weaknesses, Opportunities, and Threats (SWOT) served as on outline and a tool in identifying the core problems and challenges which the corporation is facing. With the several tools used for the analysis of the corporation?s external and internal environments, it was identified that one of the major problems that the corporation is facing is the declining market share of CMC among private schools in Kidapawan due to a stiff competition among schools in the locality. It was also identified that the Human Resource specifically its teaching workforce needs to increase its level of competency and academic qualifications to increase the value of its human capital and to be at par with other teachers in renowned educational institutions. Although the corporation is not operating in the red but its profit margin reflected to be low. Maximizing its depreciating assets and managing its account receivables are among the challenges that need to be met by the Finance area of the corporation. Lastly, CMC?s academic services as well as its curriculum need to be upgraded to be able to retain its existing students and capture prospective students to enroll in CMC. The remainder chapter of this Strategic Plan plotted out the corporate objectives and goals which eventually directed to the conceptualization and identification of several strategic options as CMC?s guide in realizing its outlined goals. With the identified core problems of CMC, it is proposed that the following strategies namely market development, organization and institutional development, and academic development should be adopted and implemented. The final chapter present the implementing program and control systems. The strategies shall be implemented within the five-year operation of the school or from school years 2012 to 2017. Within the period of five years, key result areas and performance indicators are identified. In assuring that the strategic goals are met and whether CMC is coursing in the right direction, both the activities and results will be verified as monitoring and control mechanisms are outlined and put in place. The Strategic Management Plan concludes with a projection of the annual growth which CMC may reap as a result of the implementation the strategies. The annual growths of enrollment as well as the gross and net incomes are optimistically forecasted in this Plan. With this, it is anticipated that CMC?s growth will be sustained for a longer period of time.